Multicentre randomised phase II trial of gemcitabine + platinum, with or without trastuzumab, in advanced or metastatic urothelial carcinoma overexpressing Her2. Issue 1 (January 2015) - Oudard, Stéphane; Culine, Stéphane; Vano, Yann; Goldwasser, François; Théodore, Christine; Nguyen, Thierry; Voog, Eric; Banu, Eugeniu; Vieillefond, Annick; Priou, Franck; Deplanque, Gaël; Gravis, Gwenaëlle; et al.
Abstract Aim To investigate the efficacy and safety of gemcitabine and platinum salt, with or without trastuzumab, in patients with locally advanced or metastatic urothelial carcinoma overexpressing Her2. Methods The main eligibility criterion was Her2 overexpression on immunohistochemistry (IHC 2+ or 3+) of primary tumour tissue confirmed by fluorescence in situ hybridisation (FISH). Patients were randomised to Arm A: gemcitabine 1000 mg/m2 (days 1 and 8) plus either cisplatin (70 mg/m2) or carboplatin (AUC = 5) (day 1 every 3 weeks) or Arm B: added trastuzumab (8 mg/kg loading dose, then 6 mg/kg every 21 days until progression). The primary end-point was progression-free survival (PFS). Results Among 563 screened patients, 75 (13.3%) were Her2 positive (IHC 2+/3+ and FISH+) and 61 met all eligibility criteria (median age, 64 years; 54/61 males; 50/61 baseline ECOG-PS 0-1; 11 locally advanced and 50 metastatic). There was no significant difference between Arms A and B in median PFS (10.2 versus 8.2 months, respectively, p = 0.689), objective response rate (65.5% versus 53.2%, p = 0.39), and median overall survival (15.7 versus 14.1 months, respectively, p = 0.684). In an exploratory analysis, trastuzumab-treated patients receiving cisplatin rather than carboplatin-based chemotherapy fared better (PFS: 10.6 versus 8.0; OS: 33.1 versus 9.5 months). Myelosuppression was the main grade 3/4 toxicity. A case of grade 3 cardiotoxicity and one death from febrile neutropenia occurred in arm B. Conclusion The unexpectedly low incidence of Her2 overexpression precluded the detection of a significant difference in efficacy on addition of trastuzumab to platinum-based chemotherapy with gemcitabine. However, the satisfactory tolerance of the combination warrants further studies, especially of the cisplatin-based combination, in well-defined patient subsets.